السياحة الداخلية في الجزائر: واقعها وسبل تطويرها - مخزومي, لطفي; زروخي, فيروز; عبداللاوي, عقبة (جامعة الوادي - University of Eloued, 2020)
هدفت الدراسة إلى إبراز واقع السياحة الداخلية في الجزائر وكذا الوقوف على مختلف الإجراءات الكفيلة بتطوير وتنمية القطاع السياحي، وجعله بديلا لقطاع المحروقات. توصلت الدراسة إلى أن بلادنا تزخر بإمكانيات ومقومات طبيعية، تاريخية، ثقافية وحضارية هامة مما يجعلها قبلة للسياح، إلا أن الواقع عكس ذلك فالقطاع يتخبط في جملة من المشاكل أهمها سوء التسيير، وضعف مستوى الخدمات المقدمة للزبائن، هذا ما جعل الدولة تبحث عن إيجاد حلول لذلك، منها المخطط التوجيهي للتنمية السياحية آفاق 2030 والذي يعكس لنا هدف الدولة فيما يخص التنمية المستدامة وذلك من أجل تحقيق توازن ثلاثي يشمل الرقي الاجتماعي والفعالية الاقتصادية والاستدامة البيئية The study aimed to highlight the reality of internal tourism in Algeria and also to identify various measures to develop and develop the tourism sector, and make it an alternative to the hydrocarbons sector. The study found that our country has many natural, historical, cultural and cultural potentials, which makes it a tourist destination. However, the reality is the opposite. The sector is floundering in a number of problems, the most difficult of which is poor management and poor service. To find solutions for this, including the 2030 Horizon Tourism Development Plan, which reflects the State's goal of sustainable development in order to achieve a three-pronged balance of social development, economic efficiency and environmental sustainability
Domestic tourism in Algeria: reality and ways to develop it
مقال بمجلة الدراسات المالية والمحاسبية . مج 11 ع01. ديسمبر 2020 . جامعة الوادي
Keywords: السياحة الداخلية، الجزائر، الواقع، المعوقات، الآفاق; domestic tourism; Algeria; reality; constraints; prospects